AGRICULTURAL LAND CURRENT SITUATION AND PROSPECTS - Спіжова, Марія Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article examines the problems of the agricultural land market, the existence of the moratorium on the turnover of this category of land and the legitimate ways of buying and selling such lands, the prospects for the development of the agricultural land market, the consequences of its opening on the Ukrainian territory. The views of scientists on certain issues of civil and land law are analyzed. Research methods: to determine the current situation of the agricultural land market, to identify existing ways of buying and selling land in this category, to analyze the legislation in this area, and to make proposals on the settlement of this issue. Results: the way of the further development of the agricultural land is determined. It is concluded that it is necessary to open a market for agricultural land and to settle the land turnover of this category legislatively. Discussion: the problems of national regulation of the agricultural land market and international experience in solving these problems.